Neurodiversity as a Test of Democratization in Chilean Higher Education Institutions: Beyond Access - Ibáñez Rodríguez, Laisa (PEM. Revista de Didáctica, Evaluación e Innovación, 2025)
Objective: To analyze, from a deconstructive and situated reading, how neurodiversity destabilizes and strains democratization processes in Chilean higher education beyond mere formal access, questioning the ways in which “normal” is defined, organized, and legitimized in university life. Methods: A qualitative documentary study was developed that intertwines Latin American literature on the right to education, democratization processes, and the beginnings of university life with Chilean regulatory frameworks on inclusion, disability, and autism, in addition to systematizing recent production on the trajectories of neurodivergent students in higher education institutions. Results: The analysis reveals the persistence of assumptions of normality, merit, and individual responsibility in normative and institutional discourses, as well as tensions between the rhetoric of rights, the structural segregation of the system, and the way in which mechanisms for admission, support, accessibility, and student participation are configured, which tend to reproduce adaptive rather than transformative logics. Conclusions: Neurodiversity is a test for the democratization of universities, as it highlights the obstacles to inclusion focused on access and individual adjustments, opening up a field of controversy around the definition of legitimate trajectories, quality criteria, and forms of justice that currently guide the work of Chilean higher education institutions. Key Words: democratization; neurodiversity; higher education; student trajectories.